Internal Control Systems and Follow-Up Audits of Financial Statement Quality with Government Governance as Moderating - Simatupang, Valentina; Fadli, Fadli (Goodwood Akuntansi dan Auditing Reviu, 2026)
Purpose: This study seeks to examine how weaknesses in internal control systems and follow-up on research results on the quality of local government financial reports, with good government governance serving as a moderating variable for the 2020-2023. Methodology/approach: This research employs a quantitative approach, applies purposive sampling for data collection and utilizes PLS for the analytical testing. Results/findings: Weaknesses in internal control systems are found to negative influence the quality of local government financial report. In contrast, follow-up actions on audit finding contribute positively to improving report quality. Furthermore, the implementation of good governance has been proven to lessen the negative impact arising from internal control defecies toward the quality of financial reports. Concurrently, it also reduces intensity of the association between audit follow-up actions and the overall quality of financial statements. Conclusions: Weak internal controls reduce reporting quality, while audit follow-up improves reporting outcomes. GGG strengthens mitigation of SPI weaknesses but may weaken the effectiveness of TLHP when governance practices remain procedural rather than substantive. Strengthening substantive governance practices is crucial to improving reporting integrity. Limitations: This study is limited to the period 2020-2023, covering only regency/city governments, and uses predicates for good governance, so the results do not fully represent the broader situation. Contributions: This study expands the existing discourse on public sector accountability while providing practical guidance for local governments in enhancing the quality of financial statements by reinforcing internal controls, ensuring effective audit follow-up, and institutionalizing good governance practices.